Functional morphology of the secretory pathway organelles in yeast - Vorísek, J (Microscopy research and technique, 2000)
The glycoprotein secretory pathway of yeast serves mainly for cell surface growth and cell division. It involves a centrifugal transport of transit macromolecules among organelles, whose membranes contain resident proteins needed for driving the transport. These resident membrane proteins return by retrograde vesicular transport. Apart from this, the pathway involves endocytosis. The model yeast Saccharomyces cerevisiae and vertebrate cells were found to contain very similar gene products regulating the molecular mechanism of glycoprotein transport, and the cellular mechanism of their secretion pathways was therefore also presumed to be identical. Biochemists have postulated that, in S. cerevisiae, the translocation of peptides through the endoplasmic reticulum membranes into the lumen of ER cisternae and the core glycosylation is followed by a vector-mediated transport into the functional cascade of the Golgi system cisternae and between them. This is the site of maturation and sorting of glycoproteins, before the ultimate transport by other vectors involving either secretion from the cells (exocytosis across the plasmalemma into the cell wall) or transport into the lysosome-like vacuole via a prevacuolar compartment, which serves at the same time as a primary endosome. The established cellular model of secretion deals with budding yeast; interphase yeast cells, in which the secretion is limited and which predominate in exponential cultures, have not been taken into consideration. The quality of organelle imaging in S. cerevisiae ultra-thin sections depends on the fixation technique used and on specimen contrasting by metals. The results achieved by combinations of different techniques differ mostly in the imaging of bilayers of membrane interfaces and the transparence of the matrix phase. Fixation procedures are decisive for the results of topochemical localisations of cellular antigenic components or enzyme activities, which form the basis of the following survey of functional morphology of organelles involved in the yeast secretory pathway. The existing results of these studies do not confirm all aspects of the vertebrate model of the Golgi apparatus proposed by molecular geneticists to hold for S. cerevisiae, and alternative models of the cellular mechanism of secretion in this yeast are, therefore, also discussed.
Keywords: Saccharomyces cerevisiae; Microscopy, Fluorescence; fluorescenční mikroskopie; elektronová mikroskopie; glykoproteiny; organely; Microscopy, Electron; Glycoproteins; Organelles